1995
DOI: 10.1111/j.1600-0609.1995.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a lymphotropic nature of circulating plasmacytoid monocytes: findings from a case of CD56+ chronic myelomonocytic leukemia

Abstract: Because the cells previously designated plasmacytoid T cells share major immunophenotypic features with cells of the mononuclear‐phagocyte system, they have been re‐named and are now known as plasmacytoid monocytes (PM). We describe a unique case of chronic myelomonocytic leukemia with circulating PM. The patient, a 48‐year‐old man, presented initially with refractory anemia. Four years later his general condition deteriorated, accompanied by an increase in leukocytes to 200 000/μl blood. The bone marrow histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…53,54 In our series, we found that only 5 of 23 cases (21.7%) of BPDC were positive for CLA. In the literature, at least 50 BPDC cases (about 10% to 20% of all BPDC cases) demonstrated a transformation to myelomonocytic chronic and AML, 2,6,7,11,27,30,37,[55][56][57][58][59][60][61] although to our knowledge no transformation of BPDCs to ALL has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 In our series, we found that only 5 of 23 cases (21.7%) of BPDC were positive for CLA. In the literature, at least 50 BPDC cases (about 10% to 20% of all BPDC cases) demonstrated a transformation to myelomonocytic chronic and AML, 2,6,7,11,27,30,37,[55][56][57][58][59][60][61] although to our knowledge no transformation of BPDCs to ALL has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…51,105 The induction of phenotypic and functional properties of monocytic DCs in vivo has also been described for tumor cells derived from AML and juvenile myelomonocytic leukemia. 112,113 Horny et al 114 reported a case that progressed from MDS to CMML with marked lymphotropism and atypical clusters of pDC-differentiated cells.…”
Section: Is the Association Of Hdts With Myeloid Disorders More Than mentioning
confidence: 98%
“…Approximately 10 to 20 % of cases are associated with hematologic malignancies such as myelodysplastic syndrome, chronic myeloid leukemia, chronic myelomonocytic leukemia, and acute myeloid leukemia [50]. Furthermore, in patients with chronic myelomonocytic leukemia, nodal proliferations of plasmacytoid dendritic cells (originally called plasmacytoid T or BT-zone^cells, and then plasmacytoid monocytes), have been recognized for over two decades [51][52][53][54]. Interestingly, when the skin is involved in CMML, about half the cases have infiltrates showing plasmacytoid dendritic cell lineage [55].…”
Section: Discussionmentioning
confidence: 99%